Building gender-sensitive climate-smart agriculture approaches for sustainable food-energy systems - Yami, Mastewal; Haddis, Edom; Birhane, Emiru; Kidu, Gidey (World Agroforestry Centre, 2019)
Climate change influences agricultural production and threatens the livelihoods of farming households in Africa. The impacts of climate change have been more severe for poor and marginalized peoples, especially women, than they have been for other groups in the society, due to their disadvantaged access to technologies, resources, information, and power. Conventional agriculture technology interventions aiming at improving productivity and income often do not consider social disparities and fail to enhance equitable benefit sharing among men and women. Similarly, climate-smart agriculture (CSA) approaches often fail to take into account the differences in men’s and women’s needs and capabilities for adapting to climate change and instead have an implicit male bias that privileges male needs, interests, and priorities in the distribution of opportunities and resources. The poor representation and involvement of women in decision-making processes in the agricultural sector has limited their contributions to addressing the adverse effects of climate change, energy shortages, food insecurity, and poverty. This chapter, by drawing on lessons from past and current agricultural interventions across Africa, especially Ethiopia, aims to foster understanding of the various roles and responsibilities of women in designing and implementing gender-sensitive CSA interventions to achieve a sustainable food-energy system.